(untitled) (Global Journal of Science Frontier Research, 2022)
The Geometric Algebra formalism opens the door to developing a theory replacing conventional quantum mechanics Generalizations stemming from implementation of complex numbers as geometrically feasible objects in three dimensions followed by unambiguous definition of states observables measurements bring into reality clear explanations of some weird quantum mechanical features particularly the results of double-slit experiments where particles create diffraction patterns inherent to a wave or modeling atoms as a kind of solar system